Improvised Chest Compression Training in a Multicultural Setting: Engaging International Students at a University Fair in Colombia - Jose Hernandez; Sergio Andres León-Ariza (International Journal of First Aid Education)
This manuscript explores the challenges in teaching chest compressions to international students during a university admissions fair. Traditionally conducted in Spanish, the fair saw a notable increase in non-Spanish speaking participants, prompting the Emergency Medicine Interest Group (EMIG) to adapt its teaching methods. By employing non-verbal communication techniques, AI, and improvisational strategies, we effectively engaged a multicultural audience, ensuring comprehension and participation. Our experience highlights the significance of flexibility and creativity in first aid education, emphasizing the need for inclusive teaching practices that transcend language barriers and enhance learning outcomes for diverse populations.